Students and society in the 2020s. Three future 'histories' of education and technology. Issue 1 (2nd January 2020) - Macgilchrist, Felicitas; Allert, Heidrun; Bruch, Anne
ABSTRACT: As social science fiction, this paper imagines three possible futures for education and technology. Among the most important technologies emerging today are data-aggregating technologies such as AI, affective computing, adaptive or predictive software, clouds and platforms. The paper is not, however, directed at specific technologies, but at indeterminate sociotechnical configurations. Set in 2040, it offers three 'histories' of the 2020s. Might students become (i) 'smooth users', improving themselves in the pursuit of frictionless efficiency within a post-democratic frame created by large corporations, (ii) 'digital nomads', seeking freedom, individualism and aesthetic joy as solopreneurs exploiting state regulations and algorithmic rules while stepping out of the state and deeply into the capitalist new economy, or (iii) participatory, democratic, ecological humans embedded in 'collective agency' that see institutions as spaces for exploring more equitable ways of living? The paper reflects on the future research and the political, educational and technological decisions which would make each of these three fictional future histories more or less likely.